Evaluation of maternal early obstetric warning system (MEOWS chart) as a predictor of obstetric morbidity: a prospective observational study - Singh, Anju; Guleria, Kiran; Vaid, Neelam B.; Jain, Sandhya (European journal of obstetrics & gynecology and reproductive biology, 2016)
Maternal Early Obstetric Warning System (MEOWS) chart adopted from CEMACH 2003–2005 report is based on the principle that abnormalities in physiological parameters precede critical illness. The ‘track and trigger’ of physiological parameters on this chart can aid in recognition of maternal morbidity at an early stage, ultimately halting the cascade of severe maternal morbidity and mortality. The objectives of our study were to evaluate MEOWS chart as a bedside screening tool for predicting obstetric morbidity and to correlate each physiological parameter individually with obstetric morbidity. It was a prospective observational study conducted in labour wards of Guru Teg Bahadur Hospital, Delhi, India from October 2012 to April 2014. Physiological parameters of 1065 study subjects (including pregnant women in labour >28 weeks of gestation and postpartum women up to 6 weeks after delivery) were recorded on MEOWS chart. A trigger was defined as a single markedly abnormal observation (red trigger) or the combination of two simultaneously mildly abnormal observation (two yellow triggers). Based on outcome at time of discharge, Category 1 (normal and recovered without morbidity) and Category 2 (recovered with morbidity or mortality) were defined. Chi-square and Fischer’s exact test were used for comparison between two groups. Performance of MEOWS chart was evaluated using Exact’s method. Relative risk of morbidity (odd’s ratio) and 95% confidence interval was calculated for individual parameter. p<0.05 was considered as significant. Two-hundred and eighty-four (26.6%) women triggered to abnormal zones on these charts. One-hundred and seventy-seven (16.61%) fulfilled the criteria for obstetric morbidity. MEOWS chart was 86.4% sensitive, 85.2% specific with a positive and negative predictive value of 53.8% and 96.9% respectively for prediction of obstetric morbidity. Individual parameters of MEOWS chart also had a significant correlation (p<0.05) with obstetric morbidity. MEOWS chart emerged as a useful bedside screening tool for prediction of obstetric morbidity and should be used routinely in every obstetric unit. Strict monitoring and documentation of all the vital parameters should be fundamental part of any patient’s assessment to pick up acute illness at very early stage and to make a difference in final outcome.